2017
DOI: 10.1101/gad.308254.117
|View full text |Cite
|
Sign up to set email alerts
|

Physiological protein blocks direct the Mre11–Rad50–Xrs2 and Sae2 nuclease complex to initiate DNA end resection

Abstract: DNA double-strand break repair by homologous recombination is initiated by DNA end resection, which is commenced by the Mre11-Rad50-Xrs2 complex and Sae2 in yeast. Here we report that the nonhomologous end joining factor Ku limits the exonuclease activity of Mre11 and promotes its endonuclease to cleave 5'-terminated DNA strands at break sites. Following initial endonucleolytic cleavage past the obstacle, Exo1 specifically extends the resection track, leading to the generation of long 3' overhangs that are req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 40 publications
8
124
0
Order By: Relevance
“…Other studies also recently demonstrated yeast Mre11/Rad50/Xrs2(MRX) cleavage of various protein blocks including yeast Ku, which was also manganese-dependent in vitro (10,11). Here we observe approximately the same kinetics of DNA-PK release catalyzed by MRN and CtIP as we did previously, but in magnesium-only…”
Section: Main Textsupporting
confidence: 87%
See 1 more Smart Citation
“…Other studies also recently demonstrated yeast Mre11/Rad50/Xrs2(MRX) cleavage of various protein blocks including yeast Ku, which was also manganese-dependent in vitro (10,11). Here we observe approximately the same kinetics of DNA-PK release catalyzed by MRN and CtIP as we did previously, but in magnesium-only…”
Section: Main Textsupporting
confidence: 87%
“…At single-ended breaks during replication, the nuclease activity of Mre11 was shown to be important for removal of Ku (6), suggesting that MRN catalytic processing of ends during S phase is important for recombination-mediated repair of single-ended breaks. While we and others have shown that MRN endonuclease activity is specifically stimulated by protein blocks on DNA ends (8)(9)(10)(11), we considered the possibility that DNA-PK itself constitutes a powerful block to resection, and that DNA-PK may create a critical barrier to end processing at single-ended breaks where there is no other DNA end to participate in end joining.…”
Section: Main Textmentioning
confidence: 99%
“…This is achieved by a conserved interaction between the MRN subunit NBS1 (Xrs2 in Saccharomyces cerevisiae) and ATM (Tel1 in yeast). MRE11 is likely the first nuclease to resect DSBs, which is particularly important for the processing of breaks with secondary DNA structures or protein adducts such as stalled topoisomerases or Ku (Shibata et al, 2014;Anand et al, 2016;Deshpande et al, 2016;Wang et al, 2017;Reginato et al, 2018). Beyond ATM, NBS1 also interacts with MDC1, which binds phosphorylated proteins, including H2AX (cH2AX), to amplify the DNA damage signaling beyond the vicinity of the DSB (Goldberg et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, the MRE11-RAD50-like SbcC-SbcD complex endonucleolytically cleaves DNA near blocked DNA ends (Connelly et al, 2003). In S. cerevisiae, Sae2 phosphorylated by CDK and other kinases has a critical function to promote the Mre11-Rad50 endonuclease near protein blocks (Huertas et al, 2008;Cannavo & Cejka, 2014;Wang et al, 2017;Reginato et al, 2018), while Xrs2 per se is not essential for the DNA clipping reaction in vitro (Oh et al, 2016), but may have a stimulatory function (Wang et al, 2017). In S. cerevisiae, Sae2 phosphorylated by CDK and other kinases has a critical function to promote the Mre11-Rad50 endonuclease near protein blocks (Huertas et al, 2008;Cannavo & Cejka, 2014;Wang et al, 2017;Reginato et al, 2018), while Xrs2 per se is not essential for the DNA clipping reaction in vitro (Oh et al, 2016), but may have a stimulatory function (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In both yeast and mammals, the current model for resection posits that Sae2 stimulates the endonuclease activity of Mre11 to generate an endonucleolytic cleavage of the 5 0 -terminated strands at both DSB ends (Cannavo & Cejka, 2014). The resulting nicks are entry sites for Exo1 and Dna2 nucleases that degrade long tracts of DNA in the 5 0 -3 0 direction (Mimitou & Symington, 2008;Zhu et al, 2008;Cejka et al, 2010;Niu et al, 2010;Nimonkar et al, 2011), coupled with 3 0 -5 0 exonuclease of Mre11 back toward the DNA end (Garcia et al, 2011;Shibata et al, 2014;Reginato et al, 2017;Wang et al, 2017). While Exo1 degrades the 5 0 -terminated strands within duplex DNA (Tran et al, 2002), Dna2 cleaves ssDNA flaps adjoining a duplex DNA.…”
Section: Introductionmentioning
confidence: 99%